Leveraging digital infrastructure for sustainable grain production: evidence from China - Han, Jiabin; Ge, Wenting; Chou, Yixiu (Frontiers in Sustainable Food Systems, 2024)
Introduction Agriculture faces significant challenges in ensuring global food security while minimizing resource costs and environmental impacts. The development of digital infrastructure offers transformative potential for agricultural systems and aligns with the United Nations Sustainable Development Goals. This study examines the role of digital infrastructure in enhancing grain production capacity in China, a key player in the global food system. Methods We analyzed data from 277 prefecture-level cities in China from 2011 to 2021. A double machine learning model was employed to empirically assess the impact of digital infrastructure on grain production capacity, allowing for robust insights into causal relationships. Results Results reveal that digital infrastructure significantly enhances grain production. Mechanism analysis results indicate that digital infrastructure construction drives agricultural technological advancements and farmland scale, contributing to increased production capacity. Heterogeneity analysis results show that the impact of digital infrastructure construction is significant in major grain-producing regions and the central-eastern regions, while its effects are relatively limited in grain production-consumption balanced regions, main grain consumption regions, and the western regions. Discussion The results underscore the importance of strengthening digital infrastructure in rural areas to improve grain production capacity. Tailored policy implications are suggested to enhance sustainable food production and contribute to global food security, particularly in regions with varying agricultural dynamics.